Empowering climate action through policy analysis and education in Gilgit-Baltistan: a comprehensive mixed method analysis - Fozia Fatima; Sabir Ali; Hamad Raza; Fuad Ahmad Siddiqi; Salar Ali (Frontiers in Climate)
IntroductionThe study addresses the critical gap in climate policy implementation and public education in Gilgit-Baltistan, a region highly vulnerable to climate change but underrepresented in research and policy discourse. While national climate policies exist, their translation into localized action remains ineffective due to logistical, financial, and institutional barriers.MethodsThis research aims to bridge this gap by conducting a comprehensive mixed-method analysis to assess policy shortcomings and develop targeted educational interventions. The methodology follows a four-phase approach: first, a bibliometric analysis of over 100 peer-reviewed articles and policy documents identifies research trends, gaps, and key contributors. Second, semi-structured interviews with various stakeholders, including community leaders, religious scholars, and local policymakers, reveal educational needs and awareness levels regarding climate change. The third phase involves the documentation of environmental awareness initiatives at the University of Baltistan, providing empirical evidence on existing efforts. Finally, using a Design-Based Research strategy, an educational course tailored to the socio-cultural context of Gilgit-Baltistan is developed and evaluated.ResultsFindings highlight a severe lack of interdisciplinary collaboration in Pakistan’s climate research, with Gilgit-Baltistan often overlooked in national studies. Public awareness, particularly among youth and religious leaders, is insufficient, necessitating educational programs that integrate local knowledge and practical climate action strategies. Additionally, weak policy implementation in remote regions due to governance constraints underscores the need for multi-sectoral collaboration and sustainable financial support.ConclusionThe study concludes that empowering local communities through targeted education and inclusive policymaking is essential for fostering climate resilience in Gilgit-Baltistan. It calls for urgent policy adaptation, stakeholder engagement, and structured climate education programs to ensure sustainable environmental stewardship in the region.